Photoconductivity of sensitization (ZnO/ Polystyrene(PS))Composites by Rose Bengal Dye - Rafeeg, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The photoactive behaviour of rose bengal dye sensitized (ZnO/ Polystyrene (PS)) composites was studied. Two concentrations of composite(30% Zn0/70% PS) and (50% ZnO 150% PS) with (0.05 0.1.0.3,1%)weight percentages of dye were used. The composites are photoconductive and the photoconductivity action spectrum gives the effect of the dye in the visible region. In the absence of dye within the composites, no photoactivity is observed in this region of the spectrum. The photoconductivity is affected by the dye content. Time of flight technique was used to measure response time. The rise time of the photocurrent is fast and the decay is slow.